Miangas Border Area Development Through Security, Prosperity, and Environment Approach - Hadi, Yoos Suryono; Khusaini, Moh; Fadli, Moh; Kusumaningrum, Adi (Wacana Journal of Social and Humanity Studies, 2025)
Miangas' border areas are vulnerable to various violations of territory and sovereignty, as well as law violations. This is why it is necessary to develop border areas to anticipate this vulnerability. The primary objectives of this research are to determine and analyze the influence of security, prosperity, and environmental approaches simultaneously on the development of the Miangas border area. The second is to develop a concept for border area development, applicable to land-sea borders, sea borders, and land borders. The method employed is a mixed-methods approach, combining quantitative and qualitative methods. The population and sample for quantitative research consisted of personnel in the local government and military members in Miangas. Meanwhile, the subjects for qualitative research consisted of local government and the army officials in Miangas. Quantitative research results have shown that security, prosperity, and environmental approaches have a critical positive impact on the development of border areas. Furthermore, the qualitative research results obtained from the triangulation of research subjects' opinions regarding the concept of development strategy for the Miangas border area. The results showed the idea of border areas development in Miangas, namely, the border development is carried out in a holistic, comprehensive, integrated border development system based on security, prosperity, and environmental factors thematically and spatially, with measurements for success, namely productivity, efficiency, and community participation through a combination of top-down and bottom-up systems.   Keywords: Miangas, border area development, security, prosperity, environmental